2019
DOI: 10.1017/s0047279419000722
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Women on Board: The Social Policy Implications of Gender Diversity in Top Jobs

Abstract: This paper argues that analyses of the gendered character of welfare states should be broadened to include women’s share of board and executive roles, as well as the affirmative-action policies (e.g. gender boardroom quotas) that help to overcome the gender stereotypes (e.g. women are ‘nice’, men are ‘assertive’) and opaque selection procedures at the root of this. Such indicators may seem beyond the remit of social policy analysis, which is concerned foremost with the analysis of ‘social risk’. However, drawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 83 publications
0
13
0
1
Order By: Relevance
“…Larrieta-Rubín de Celis, Velasco-Balmaseda, de Bobadilla, Alonso-Almeida, and Intxaurburu-Clemente (2015) showed that the presence of women directors positively influences the implementation of CSR practices related to achieving gender equality, such as remuneration, training and career development, and work-life balance measures. Kowalewska (2020) reported that women in less senior positions within the company benefit from the presence of women directors by earning higher salaries, which reduces wage gaps (Stainback, Kleiner, & Skaggs, 2016).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Larrieta-Rubín de Celis, Velasco-Balmaseda, de Bobadilla, Alonso-Almeida, and Intxaurburu-Clemente (2015) showed that the presence of women directors positively influences the implementation of CSR practices related to achieving gender equality, such as remuneration, training and career development, and work-life balance measures. Kowalewska (2020) reported that women in less senior positions within the company benefit from the presence of women directors by earning higher salaries, which reduces wage gaps (Stainback, Kleiner, & Skaggs, 2016).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The resolution deems it of the 'utmost importance' to have more female role models and to increase the number of women in leadership positions, in decision-making and on corporate boards. Having women on corporate boards is in itself intrinsically important, but it also has trickle-down benefits for women in terms of employment outcomes and culture (Kowalewska, 2020(Kowalewska, , 2021…”
Section: Overarching Context and Legislationmentioning
confidence: 99%
“…Companies with higher numbers of women on board can break down stereotypes and have a trickle-down effect on the rest of the employees within the company. Diverse boards can therefore influence internal cultural changes and provide role models that encourage women to pursue leadership roles 7 .…”
Section: Gender Diversity Leads To Better Management and Boosts Innov...mentioning
confidence: 99%